A qualitative study on feedback provided by students in nurse education - Chan, Zenobia C.Y.; Stanley, David John; Meadus, Robert J.; Chien, Wai Tong (Nurse education today, 2017)
This study aims to help nurse educators/academics understand the perspectives and expectations of students providing their feedback to educators about teaching performance and subject quality. The aim of this study is to reveal students' voices regarding their feedback in nurse education in order to shed light on how the current student feedback practice may be modified. A qualitative study using focus group inquiry. Convenience sampling was adopted and participants recruited from one school of nursing in Hong Kong. A total of 66 nursing students from two pre-registration programs were recruited for seven focus group interviews: one group of Year 1 students (n=21), two groups of Year 3 students (n=27), and four groups of Final Year students (n=18). The interviews were guided by a semi-structured interview guideline and the interview narratives were processed through content analysis. The trustworthiness of this study was guaranteed through peer checking, research meetings, and an audit trail. The participants' privacy was protected throughout the study. Four core themes were discerned based on the narratives of the focus group interviews: (1) “timing of collecting feedback at more than one time point”; (2) “modify the questions being asked in collecting student feedback”; (3) “are electronic means of collecting feedback good enough?; and (4) “what will be next for student feedback?”. This study is significant in the following three domains: 1) it contributed to student feedback because it examined the issue from a student's perspective; 2) it explored the timing and channels for collecting feedback from the students' point of view; and 3) it showed the preferred uses of student feedback. •Reveals students’ expectations of collecting feedback from their viewpoint.•Shows educators how they should manage student feedback to maximize the outcomes.